"Confrontational but Not Violent": An Assessment of the Potential for Violence by the Anti-Authority Community in Canada. Issue 8 (16th November 2020) - Perry, Barbara; Hofmann, David C.; Scrivens, Ryan
ABSTRACT: Despite a pervasive concern among law enforcement and security agencies, there are relatively few academic explorations of the likelihood of violence associated with anti-authority activists from groups such as the Freemen-on-the-Land, Sovereign Citizens, and similar movements within Canada. In order to begin addressing this gap in knowledge, this article uses a multi-method approach to explore and assess the potential for violence by the Canadian anti-authority community against the state in particular. Data were gathered from interviews with law enforcement, lawyers, judges, notaries, and movement adherents (n = 32), as well as from the analysis of open source data which included media reports, court documents, and movement websites. Results suggest that there are three distinct classes of violent activity, directed specifically at the state and state actors, that are prevalent among Canadian anti-authority movements: a) offensive/extremist violence; b) defensive/reactionary violence; and c) harassment and intimidation. The article concludes with a discussion of two emerging areas of concern related to Canadian anti-authority violence and responses to the anti-authority community in Canada.